Study of the overregulation of the Southern Buh river - Mats, Andrii (Видавництво Львівської політехніки, 2024)
In the course of the study, the volume of reservoirs in the Southern Buh River basin was studied; the ratio of the areas of the water mirror of the reservoirs of the river basin by region is determined; the dynamics of the capacity of the reservoirs of the Southern Buh River basin over a certain period, as well as the dynamics of the capacity of the reservoirs of the Southern Buh River within the Mykolaiv region, are evaluated; the density of reservoirs along the river bed is analyzed. It is determined that the largest useful volume of reservoirs falls in Mykolaiv region (34%). It is shown that the largest area of the water mirror is located in Vinnytsia region (31%), and the smallest – is in Kyiv and Odesa regions (2%). It is shown that the largest increase in the volume of reservoirs falls on the period of the 60s of the twentieth century. It is determined that the average density of artificial reservoirs is about one reservoir for every 10 km of the river, which indicates the critical overregulation of the river. A significant level of river regulation, along with several advantages, has environmental challenges, especially in the context of current climate change issues. These issues require further research in the direction of studying the optimality of the volume of reservoirs because of maintaining the river's ability to self-regulate processes, preserving the unique hydroecosystems of the river, which should be taken into account in managing water resources.
Keywords: Southern Buh; overregulation of the river; reservoirs